Transforming Elementary School Students’ Science Literacy through Scratch-Based E-Modules Integrated with Islamic Value - Ismail, Ismail; Moh. Wardi, Moh. Wardi (Universitas Pendidikan Ganesha, 2025)
Science education at the elementary school level is an important foundation in forming students' initial understanding of the universe, as well as fostering critical thinking and problem-solving skills. This study aims to explore the effectiveness of Scratch-based e-modules integrated with Islamic values in improving students' scientific literacy. This study used a quasi-experimental design and quantitative methodology. The population of this study was all elementary school students totaling 197 students. Sampling was carried out by purposive sampling. Data collection used a test instrument designed to measure students' scientific literacy. The data analysis method used validity, reliability and hypothesis testing using the N-Gain test. The results of the study revealed that the use of Scratch-based e-modules combined with Islamic principles can improve students' conceptual understanding of science, this program helps them develop moral principles such as accountability and environmental awareness. These findings highlight the importance of contextual and comprehensive teaching strategies that combine technology with religious and cultural values. By presenting a learning model that can be applied in various cultural situations, these findings also add to knowledge in the field of education.